λ -DEFINABILITY OF BUILT-IN McCARTHY FUNCTIONS AS FUNCTIONS WITH INDETERMINATE VALUES OF ARGUMENTS - Nigiyan, S.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2019)
The built-in functions of programming languages are functions with indeterminate values of arguments. The built-in McCarthy functions car , cdr , cons , null , atom , if , eq , not , and , or , are used in all functional programming languages. In this paper we show the λ -definability of the built-in McCarthy functions as functions with indeterminate values of arguments. This result is necessary when translating typed functional programming languages into untyped functional programming languages.